Advances in geopolymer composites with natural reinforcement - Assaedi, H.; Alomayri, T.; Shaikh, Faiz; Low, I. (2018)
© 2018 Elsevier Ltd. All rights reserved. When compared to their synthetic counterparts, natural fibers represent an environmentally friendly alternative by virtue of several attractive attributes that include low density, lower cost, nontoxicity, and ease in processing, renewability, and recyclability. Moreover, the use of natural fibers in polymer matrix composites has the potential to produce materials with higher specific strength and specific modulus due to their low density. In this chapter, geopolymer matrices reinforced with cotton fabrics (CF) and flax fabrics (FF) have been fabricated and characterized. The thermal stability, physical properties such as density and porosity, and the mechanical properties such as flexural strength, flexural modulus, and fracture toughness were evaluated. Results indicated that both FF and CF have significant impact in improving the mechanical properties of geopolymers. However, FF-reinforced geopolymer composites showed better mechanical behavior as compared to geopolymer-reinforced with CF.